The Relationship between Knowledge and Attitudes of Pregnant Women Towards the Implementation of Pregnancy Exercises at the Dolik Community Health Center - Wairna Ladjima; Rani Safitri (Green Health International Journal of Health Sciences Nursing and Nutrition, 2026)
Pregnancy is a crucial period that requires intensive maternal health monitoring. Prenatal exercise is a non-medical intervention that is beneficial for improving physical fitness, reducing pregnancy complaints, and preparing mothers for childbirth. This study aims to determine whether there is a relationship between the knowledge and attitudes of pregnant women and the implementation of prenatal exercise at the Dolik Community Health Center. This study design was quantitative descriptive analytic with a cross-sectional approach. The sample consisted of 28 pregnant women selected using purposive sampling. Data were collected through a structured questionnaire regarding knowledge, attitudes, and implementation of prenatal exercise, then analyzed using the Chi-Square test. The results showed that the majority of pregnant women had good knowledge (60.7 %) and a positive attitude towards prenatal exercise (64.3%). Bivariate analysis showed a significant relationship between knowledge and implementation of prenatal exercise (p = 0.021) and between attitude and implementation of prenatal exercise (p = 0.034). Mothers with good knowledge and positive attitudes were more likely to regularly participate in prenatal exercise. This study shows a relationship between knowledge and attitudes and implementation of prenatal exercise, so increasing education and fostering positive attitudes are important strategies to encourage participation of pregnant women.